EFFECT NICKEL AND QUENCH-TEMPER PROCESS ON MECHANICAL AND CORROSION PROPERTIES OF ASTM A588 WAETHERING STEEL - Rohmah, Miftakhur -; Ramadhan, Gilang; Irawan, Dedi; Utama, Dedi Pria; Romijarso, Toni Bambang (National Research and Innovation Agency (BRIN), 2022)
The mechanical improvement and